Research excellence: nurturing competencies for successful research leaders / NoorAileen Ibrahim and Sheema Liza Idris - Ibrahim, NoorAileen; Idris, Sheema Liza (2024)
Academy of Language Studies of UiTM Perak Branch or Akademi Pengajian Bahasa (APB) had organized a Strategic Planning Workshop on the 31st of January 2024 at Bilik ILQAM UiTM Seri Iskandar, Perak. This workshop is divided into 5 sessions. The speaker for the third session of the day is the honourable Professor Dr Zuraidah Mohd Sanusi, Principal Fellow of the Accounting Research Institute Universiti Teknologi MARA.